Bone loss in HIV: a contemporary review. Issue 6 (December 2015) - Hileman, Corrilynn O.; Eckard, Allison Ross; McComsey, Grace A.
Abstract : Purpose of review: Because of antiretroviral therapy (ART), people are living with HIV infection longer than ever before. As this patient group ages, it is expected that medical comorbidities such as osteoporosis and fragility fractures will increase. The purpose of this review is to address the epidemiology and what is known regarding the pathogenesis of bone loss in people living with HIV infection with a focus on recently published literature. Recent findings: HIV-infected individuals are at increased risk for low bone mineral density and bone fractures. The cause of bone loss in HIV is multifactorial including traditional risk factors some of which disproportionately affect HIV-infected individuals and alterations in bone metabolism due to ART, HIV viral proteins and chronic inflammation. Lifestyle modification, changing ART, calcium and vitamin D supplementation and pharmacologic treatment for osteoporosis may all be employed to abrogate bone loss in this patient group. Summary: Clinicians should be aware of the contributors to bone loss in people living with HIV in order to recognize high-risk individuals and to take appropriate steps to address modifiable risk factors to prevent future fracture.